The Academic Language of Climate Change: An Introduction for Students and Non-native Speakers - Manolas, Evangelos; Leal Filho, Walter (Emerald Publishing Limited, 2022)
Offering an interdisciplinary introduction to climate change and its intersection with numerous industries and facets of life, this book provides a necessary and welcome introduction for undergraduate and graduate students, and any non-native English speakers seeking to engage with climate change research.